Slow walking as a passage to dis/appearing. (1st December 2016) - Heimonen, Kirsi
In this article I focus on the experience of slow walking in selected outdoor (and indoor) public locations as a part of an ongoing artistic study. A series of slow walks function as corporeal acts towards meaning making by a dancer-researcher in the framework of a phenomenological approach. In the act of slow walking and standing the notion of appearance and disappearance is discussed in relation to the 'I', in detachment and passivity, and how this perspective challenges the previous habitual ways of being. The writings of Simone Weil, particularly her concept of the de-creation of the 'I', are discussed with these experiences of walking and standing. The walks happen simultaneously with the writing: the walking continues its echoes in the body of the dancer-researcher as she writes. The flux between holding and releasing, uncertainty, and nothingness run through the article, though the respect towards the hidden nature of corporeal knowledge, non-knowledge, exists. The lived experience of the walks form the method, as well as the results; and the method of vulnerability shows the possibilities of communication with people and environments through one's corporeality so that readers can have the benefit of discovering all that is embedded in artistic studies.